ECAT‐V: where clinical and research training meet. (19th October 2013) - Argyle, David J.; Iredale, John P.; Jackson, Andrew P.; Walker, Brian R.
Abstract : The University of Edinburgh is currently inviting applications for a unique training programme intended to develop a new generation of veterinary researchers, who are able to conduct internationally competitive research while still being grounded in clinical practice. Modelled on the Edinburgh Clinical Academic Track (ECAT) programme for medical trainees, the ECAT‐V programme will allow successful applicants to develop both their clinical and research skills. Here, David Argyle, head of the Royal (Dick) School of Veterinary Studies, and his medical colleagues, John Iredale, Andrew Jackson and Brian Walker, describe the initiative and explain why it is important